Reverse subsidies in global monopsony capitalism : gender, labour, and environmental injustice in garment value chains - Nathan, Dev (Cambridge : Cambridge University Press, 2022)
This book provides a firm analytical base to discussions about injustice and the unequal distribution of gains from global production in the form of global monopsony capitalism. It utilizes the concept of reverse subsidies as the purchase of gendered labour and environmental services below their costs of production in garment value chains in India and other garment producing countries, such as Bangladesh and Cambodia. Environmental services, such as freshwater for garment manufacture and land for cotton production, are degraded by overuse and untreated waste disposal. The resulting higher profits from the low prices of garments are captured by global brands, using their monopsony position, with few buyers and myriad sellers, in the market. This book links the concept of reverse subsidies with those of injustice, inequality and sustainability in global production.
Title from publisher's bibliographic system (viewed on 21 Jan 2022).
Keywords: Clothing trade; Clothing workers